The “freedom of teaching” and the foundation of political action of private sector in Brazil between 1945 and 1964 - Alvaro de Oliveira Senra (Revista Brasileira de História da Educação, 2012)
This article discusses the use of the concept of “teaching freedom” by the private school education to defend their interests in education in Brazil during the democratic period between the years 1945 and 1964. Based on the hegemony of the Catholic Church, who worked within the unions and which had its own entity, the Association of Catholic Education in Brazil (AEC), private education was based on an argument of a non-capitalist, founded on law families.